European policy in the face of the reflections of the crisis Ukrainian-Russian 2022 on European Energy security - KABOUCHE, Seif-eddine (Journal of Human Sciences, 2023)
Energy security is the most prominent challenge facing the European Union, especially after the Russian military operation in Ukraine in February 2022, as that military operation had serious repercussions on the energy security of the European Union countries, albeit to a varying degree from one country to another, and this is what was imposed on the EU countries. Intensifying efforts and working collectively to meet its energy needs, and reducing the negative repercussions of energy insecurity on all political, economic and social aspects, by taking a set of effective measures by diversifying regions and sources of supply by finding new suppliers, and Resorting to alternative energy resources and rational management of current energy reserves, which are measures that were enough for the countries of the Union to overcome these dangerous repercussions in the near term of the impact of the Russian military operation in Ukraine.